Determinasi Pertumbuhan Ekonomi dan Upah Minimum Terhadap Penyerapan Tenaga Kerja di Tulungagung - Gofur Rofik Amanu; Nafik Umurul Hadi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this study is to determine the effect of economic growth and minimum wage on employment in Tulungagung from 2008-2022. This research is descriptive quantitative type, using multiple linear regression analysis and the data used are secondary data of ADHK GRDP, district minimum wage, and working population of Tulungagung obtained from the Tulungagung Central Statistics Agency (BPS). The results showed that the Economic Growth variable had a partially significant negative effect on employment in Tulungagung Regency with T value < T table (-5,213 < 1.782) and significant 0,000 < 0,05. Minimum Wage variable had a partially significant positive effect on employment in Tulungagung Regency with T value > T table (5,830 > 1.782) and significant 0,000 < 0,05. Meanwhile, Economic Growth and Minimum Wage simultaneously have a positive and significant effect on Labor absorption in Tulungagung Regency with F value > F table (17,003 > 3,89) and significant 0,000 < 0,05.